Pelatihan Fasohah Al-Qur’an di Masjid Jami’ Darussholah Pakong Modung Bangkalan - Ahmad Bahrudin; Achmad Ghufron; Umar Zakka (Universitas 45 Surabaya, 2023)
Al-Qur'an fasohah training at the Jami' Darussholah Pakong Modung Mosque, Bangkalan. The problem raised in this community service activity is related to the ability to read the Qur'an which is very important from the da'wah of Muslims, so learning about how to read the Koran must be conveyed intensely and easily understood by the congregation (may local language). To find alternative solutions to the above, Al-Qur'an fasohah training was held at the Jami' Darussholah Pakong Modung Bangkalan Mosque. The objectives of this PkM activity are: 1) Relating to the problem of the ability to recite the Qur'an for young people in Pakong village for the continuation of their studies. 2) Relating to the problematic knowledge of the theory of reciting the Koran in the Pakong village community. 3) Relating to the urgency of the ability to read the Koran. 4) Relates to the urgency of the ability to understand the theories of reciting the Koran and its application. 5) Relating to the use, direction and maximization of the potential for reading the Koran in the Pakong village community. Based on the agenda for Fasohah al-Qur'an training activities on Tuesday night. Can provide knowledge and increase their ability to read the Koran, so that automatically their knowledge of reading the Koran will increase and be insightful.